The Relationship Between Self-Control and Non-Suicidal Self-Injury in Adolescent Psychiatric Outpatients: Exploring the Role of Self-Control - Zhenhua Chen; Jie Xu; Ronghua Zhang; Yuxuan Wang; Ziwei Shang (Children)
Background: Non-suicidal self-injury (NSSI) is a significant public health concern that threatens the physical and mental health of adolescents. Given its high prevalence among adolescents, understanding the characteristics and contributing factors of NSSI is crucial. This study aimed to characterize NSSI and examine the relationship between self-control and NSSI among adolescent psychiatric outpatients. Method: This study was conducted in a psychiatric department of a hospital in Hubei Province, China, involving 206 adolescent psychiatric outpatients (135 females, 12–18 years old). Assessments included the Ottawa Self-Injury Inventory (OSI), the Self-Control Scale (SCS), and a self-designed sociodemographic questionnaire. Result: In this sample, 77.18% reported a history of NSSI. The prevalence of NSSI was significantly higher in females than in males (χ2 = 19.059, p < 0.01). The NSSI group had significantly lower self-control scores compared to the non-NSSI group (F = 27.458, p < 0.01). In the NSSI group (n = 156), self-control was negatively associated with NSSI frequency and fully mediated by NSSI function. Conclusions: These findings highlight the complete mediating role of NSSI function between self-control and NSSI frequency, offering insights for future prevention and intervention efforts.